Pengaruh Keterampilan Big Data Analytics, Keterampilan Diagnostik, dan Professional Skepticism Terhadap Keterampilan Akuntansi Forensik pada Akuntan Generasi Z di Era Kompleksitas Data dan Inovasi Terbuka - Trie Indah Aprilia Putri; Hasnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of Big Data Analytics Skills, Diagnostic Skills, and Professional Skepticism on Forensic Accounting Skills among Generation Z accountants in the era of data complexity and open innovation. Using a quantitative approach, data was collected from 237 respondents aged 20-27 with at least six months of professional accounting experience in Jakarta. Analysis using SPSS 30 revealed that only Professional Skepticism significantly influenced Forensic Accounting Skills, while Keterampilan Big Data Analytics and Diagnostic Skills had no significant impact. These findings emphasize the important role of Professional Skepticism in improving forensic accounting, especially in dealing with complex issues such as fraud.